Extracellular proton modulates GABAergic synaptic transmission in rat hippocampal CA3 neurons - Zhou, Chunyi (2007)
Acidification, which occurs in some pathological conditions, such as ischemia and hypoxia often induces neurotoxicity. The activation of acid sensing ion channels (ASICs), which are highly permeable to calcium, has been considered the main target responsible for calcium overload in ischemic/hypoxia brain. However, the influence of extracellular proton on GABAergic synaptic transmission is not well understood. In the rat (aged 6–12 postnatal days) hippocampal CA3 neurons dissociated with an enzyme free, mechanical method, we show that raising the extracellular pH (to 8.5) or lowering it (to 6.0) significantly increased or decreased, respectively, the frequency and the amplitude of spontaneous inhibitory postsynaptic currents mediated by γ-aminobutyric acid A (GABA(A)) receptors. Interestingly, these modifications were not altered by amiloride (100 μM, an antagonist for ASICs), tetrodotoxin (0.5 μM, a sodium channel blocker), cadmium (100 μM, a non-selective blocker for voltage gated calcium channels), or a medium containing low calcium (0.5 mM). Significantly, changes in extracellular pH biphasically altered the peak amplitude of the currents elicited by extracellular GABA in CA3 neurons dissociated with enzyme. Raising the extracellular pH (to 8.5) or lowering it (to 6.5) shifted the concentration-response curves of GABA to the left or right, respectively, without altering the maximal responses. These data suggest that proton alters the apparent affinity of GABA receptors for agonist. Thus, extracellular proton modifies GABAergic synaptic transmission both presynaptically and postsynaptically, and this could be independent of ASICs and voltage gated calcium channels. Our finding may constitute a new mechanism underlying acidification-induced neurotoxicity.